2015
DOI: 10.1161/circulationaha.114.010765
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Muscle Sympathetic Reflex Activation in Human Heart Failure

Abstract: Background-Muscle sympathetic activation in heart failure with reduced ejection fraction (HFrEF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 48 publications
(70 reference statements)
7
76
1
1
Order By: Relevance
“…We speculate that this could be the result of divergent effects of LBPP on mean blood pressure (distending) and pulse pressure (pulsatile) responses, or alternatively, that the small magnitude (≤4 mm Hg) changes in blood pressure are not sufficient to evoke detectable changes in PWV. With respect to sympathetic outflow, cardiopulmonary baroreceptor loading has been reported to elicit smaller reflex modulations in MSNA compared with cardiopulmonary unloading 34. Whether a similar hysteresis exists with respect to the interaction of peripheral sympathetic activity on PWV is unknown, but may explain prior null findings under ganglion blockade in young participants 29, 30.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…We speculate that this could be the result of divergent effects of LBPP on mean blood pressure (distending) and pulse pressure (pulsatile) responses, or alternatively, that the small magnitude (≤4 mm Hg) changes in blood pressure are not sufficient to evoke detectable changes in PWV. With respect to sympathetic outflow, cardiopulmonary baroreceptor loading has been reported to elicit smaller reflex modulations in MSNA compared with cardiopulmonary unloading 34. Whether a similar hysteresis exists with respect to the interaction of peripheral sympathetic activity on PWV is unknown, but may explain prior null findings under ganglion blockade in young participants 29, 30.…”
Section: Discussionmentioning
confidence: 98%
“…Immediately following discrete brachial blood pressure measurements, cf‐PWV was measured at minute 7 and minute 9 during both baselines and at minute 9 and 11 during each pressure stimulus. In a subset of participants, continuous measures of MSNA were also collected over the entire duration of study to provide a direct marker of peripheral sympathetic activity 34, 35. To permit all variables to return to baseline levels, participants were given at least 8 minutes of quiet rest before repeating the protocol with the alternate pressure stimulus.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…44 In heart failure, individual units within the multiunit MSNA envelope can respond independently and oppositely to different afferent baroreceptor reflex stimuli. 46 Dempsey et al 10 have suggested, on the basis of functional imaging studies, that some brain cells may be hypoxia sensitive, whereas other neuronal tissue may be selectively sensitive to arousal or sleep disruption. 17,18 We speculate, on the basis of these present findings, that both OSA and arousal can induce selective independent changes in cortical or brain stem centers governing or augmenting the firing rate of individual postganglionic sympathetic fibers thus altering such single-unit firing properties.…”
Section: Discussionmentioning
confidence: 99%